The Phenomenon of Mass Marriages in Kampung Matfa - Tri Handini; Syawaluddin Nasution (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2023)
This article aims to describe Mafta and the phenomenon of mass marriage occurring in Kampung Mafta and to explore the underlying reasons behind this practice. The qualitative method is used with interviews, field observations, and documentation as data collection techniques. This study shows MAFTA Indonesia prioritizes the education and practical application of Islamic teachings, as well as promoting citizenship responsibility. Its core philosophy revolves around â€œtogethernessâ€ and â€œcompassion,â€ fostering equality among its members. Mass weddings in Kampung Matfa serve to strengthen the bonds within the community and dispel negative perceptions. Tuan Imam provides spiritual guidance, emphasizing virtues such as kindness and obedience to Allah and the Prophet. He teaches love for Allah, the Prophet, family, and nature, instilling a sense of unity within the community. The mass weddings in Kampung Matfa teach the values of love, unity, and equality while promoting goodness and citizenship responsibility.